2011
DOI: 10.1007/s00128-011-0466-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Trends of PM2.5 and PM10 in Ambient Air and Their Correlation in Ambient Air of Lucknow City, India

Abstract: The PM(10) concentration (μg/m(3)) in Lucknow city at 4 locations in three different seasons ranged between 148.6-210.8 (avg. 187.2 ± 17.1) during summer, 111.8-187.6 (avg. 155.7 ± 22.7) during monsoon and 199.3-308.8 (avg. 269.3 ± 42.9) during winter while PM(2.5) ranged between 32.4-67.2 (avg. 45.6 ± 10.9), 25.6-68.9 (avg. 39.8 ± 4.6) and 99.3-299.3 (avg. 212.4 ± 55.0) during respective seasons. The mass fraction ratio of PM(2.5) ranged between 0.22-0.92 (avg. 0.42 ± 0.26) and was significantly high during w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 15 publications
2
14
0
3
Order By: Relevance
“…The poor road and traffic system, use of biomass as a domestic fuel, practice of crop burning, and upliftment of soil and dust (resuspended) may be responsible for the high load of PM at the present study site. The concentration of PM at the present study site is lower than that found in Kanpur, Delhi, Lucknow, Udaipur, and Punjab . The characteristics of these cities are similar to those of the present study site.…”
Section: Resultssupporting
confidence: 70%
“…The poor road and traffic system, use of biomass as a domestic fuel, practice of crop burning, and upliftment of soil and dust (resuspended) may be responsible for the high load of PM at the present study site. The concentration of PM at the present study site is lower than that found in Kanpur, Delhi, Lucknow, Udaipur, and Punjab . The characteristics of these cities are similar to those of the present study site.…”
Section: Resultssupporting
confidence: 70%
“…PM 10 is higher in May (220 ± 73 mg m À3 ) due to increased dust concentration and follows the columnar AOD trend (Tiwari et al, 2013a), while it decreases significantly in June and July (120 ± 44 mg m À3 ) due to rainy washout. The PM 10 levels indicate that Varanasi is one of the heavily aerosol laden sites in India with concentrations comparable to other polluted industrial and urban centres over IGP (Sharma and Maloo, 2005;Chelani et al, 2010;Pipal et al, 2011;Dey et al, 2012;Pandey et al, 2012;Guttikunda, and Calori, 2013;Tiwari et al, 2009Tiwari et al, , 2013bTiwari et al, , 2014a. Fig.…”
Section: Temporal Variation Of Pm 10 and Aerosol Componentsmentioning
confidence: 92%
“…Both particulates vary in space and time, subject to the same weather conditions, providing a valuable determinant of horizontal correlation [29], [30]. Vertical correlations between PM 2.5 and PM 10 concentrations were calibrated in terms of the observed data.…”
Section: Methodsmentioning
confidence: 99%